Meta-analysis of cohort and case-control studies of type 2 diabetes mellitus and risk of atrial fibrillation - Huxley, Rachel; Filion, K.; Konety, S.; Alonso, A. (2011)
Atrial fibrillation (AF) is 1 of the most clinically diagnosed cardiac disturbances but little is known about its risk factors. Previous epidemiologic studies have reported on the association between diabetes mellitus (DM) and subsequent risk of AF, with inconsistent results. The aim of this study was to conduct a meta-analysis of published studies to reliably determine the direction and magnitude of any association between DM and AF. A systematic review and meta-analysis was conducted. PubMed and EMBASE were searched to identify prospective cohort and casecontrol studies that had reported on the association between DM and other measurements of glucose homeostasis with incident AF by April 2010. Studies conducted in primarily high-risk populations and participants in randomized controlled trials were excluded. Seven prospective cohort studies and 4 casecontrol studies with information on 108,703 cases of AF in 1,686,097 subjects contributed to this analysis. The summary estimate indicated that patients with DM had an approximate 40% greater risk of AF compared to unaffected patients (relative risk [RR] 1.39, 95% confidence interval [CI] 1.10 to 1.75, p for heterogeneity <0.001). After correcting for publication bias, the RR was 1.34 (1.07 to 1.68). Studies that had adjusted for multiple risk factors reported a smaller effect estimate compared to age-adjusted studies (RR 1.24, 95% CI 1.06 to 1.44, vs 1.70, 1.29 to 2.22, p for heterogeneity = 0.053). The population-attributable fraction of AF owing to DM was 2.5% (95% CI 0.1 to 3.9). In conclusion, DM is associated with an increased risk of subsequent AF but the mechanisms that may underpin the relation between DM and AF remain speculative. © 2011 Elsevier Inc. All rights reserved.